Solid waste management in rural areas: A narrative review - Silva, Marcelo Henrique Toscano; Beraldo, Keile Aparecida; Gracio, Heber Rogerio (Seven Editora, 2024)
In Brazil, the deficit in access to basic sanitation services, of which waste management is a part, is also concentrated in rural areas, which is worrisome, given the importance of the services for the promotion of human health and environmental quality. Thus, the objective of the present study was to conduct a narrative review of the literature on solid waste management (SRM) in rural areas. To this end, the review was carried out in a non-systematic manner, from January to July 2023, using the following databases: Scopus, Web of Science, Science Direct and Google Scholar. The results are discussed in two sections: 1) concepts and situational overview; and 2) empirical studies. From the literature analyzed, it was found that MRS in rural areas represents a concern in several countries, however, there are additional challenges for economically developing countries. Specifically in Brazil, historically, there has been an inefficiency and even non-existence of the service, which leads the communities themselves to establish forms of management, which are often inadequate. Thus, the information collected in this study can contribute to a broad understanding of the situation of the MRS in Brazilian rural areas, in addition to the identification of the different aspects that have been worked on in the literature, in which emphasis was placed on the situational diagnosis of waste management. DOI:https://doi.org/10.56238/sevened2024.007-003